Integrin-specific control of focal adhesion kinase and RhoA regulates membrane protrusion and invasion. - Patricia Costa; Tim M E Scales; Johanna Ivaska; Maddy Parsons (PLoS ONE)
Cell invasion through extracellular matrix (ECM) is a hallmark of the metastatic cascade. Cancer cells require adhesion to surrounding tissues for efficient migration to occur, which is mediated through the integrin family of receptors. Alterations in expression levels of β1 and β3 integrins have previously been reported in a number of human cancers. However, whether there are specific roles for these ubiquitous receptors in mediating cell invasion remains unclear. Here we demonstrate that loss of β1 but not β3 integrins leads to increased spread cell area and focal adhesion number in cells on 2D immobilized fibronectin. Increased adhesion numbers in β1 knockdown cells correlated with decreased cell migration on 2D surfaces. Conversely, cells depleted of β1 integrins showed increased migration speed on 3D cell-derived matrix as well as in 3D organotypic cultures and inverted invasion assays. This increased invasive potential was also seen in cells lacking β3 integrin but only in 3D cultures containing fibroblasts. Mechanistically, in situ analysis using FRET biosensors revealed that enhanced invasion in cells lacking β1 integrins was directly coupled with reduced activation of focal adhesion kinase (FAK) and the small GTPase RhoA resulting in formation of enhanced dynamic protrusions and increased invasion. These reductions in FAK-RhoA signal activation were not detected in β3 knockdown cells under the same conditions. This data demonstrates a specific role for β1 integrins in the modulation of a FAK-RhoA-actomyosin signaling axis to regulate cell invasion through complex ECM environments.